Soil water restriction and performance of soybean seeds treated with phytosanitary products - Everson R. Carvalho; Debora K. Rocha; Eusímio F. Fraga Júnior; Raquel M. de O. Pires; Thaísa F. Oliveira; Amanda C. Penido (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The effect of phytosanitary products on the initial performance of soybean crops under soil water deficit conditions was determined via seed treatment before and after storage. A randomized block design was used in a split-plot scheme with four replicates. Plots with and without soil water deficit were established in a previously cultivated field. The subplots consisted of the following phytosanitary chemical seed treatments: Abamectin + thiamethoxam + fludioxonil + metalaxyl-M + thiabendazole, Fipronil + pyraclostrobin + methyl thiophanate, Fludioxonil + metalaxyl-M + thiabendazole, Fludioxonil + metalaxyl-M, Tiofanato-metílico+Fluazinam, Carbendazim + tiram, Chlorantraniliprole, Acetamiprid, Fipronil, Thiamethoxam, Imidacloprid + thiodicarb, and a control (water). The emergence percentage, emergence speed index, mean emergence time, and seedling dry matter were evaluated immediately after phytosanitary treatment and after six months of storage for the treated seeds. Initial seedling development was impaired by soil water deficit, with a mean matric potential of -26 kPa at a soil depth of 5 cm and -20 kPa at 10 cm. The treatment of seeds with fungicides favored the initial development of soybean seedlings, especially under soil water restriction. It was determined that treatment with insecticidal and nematicides for six months in advance affects seed vigor and the initial performance of soybean crops with different intensities depending on the active ingredient.